Skin manifestations of connective tissue diseases in childhood. 3. Lupus erythematosus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Lupus erythematosus (LE) is the less frequent connective tissue disease in childhood, not only as compared with scleroderma, but even with dermatomyositis. 7 out of our 10 cases observed in childhood are girls of peripuberal age. Discoid and systemic LE do not significantly differ from the adult form. On the other hand, neonatal LE is characteristic of infantile age. It is due to transplacentally passively acquired autoantibodies, mainly antiRo-SSA. However, in contrast with other transplacentally transmitted dermatoses, neonatal LE is much more persistent and sometimes is followed by sistemic LE, supporting the hypothesis that the disease in these infants is associated with a particular genetic predisposition, besides the presence of passively acquired autoantibodies. The problem of the prevention of neonatal LE is particularly emphasized.